ADA Score for Predicting Cardiovascular Events in Atrial Fibrillation - Pignatelli, Pasquale; Valeriani, Emanuele; Pastori, Daniele; Bartimoccia, Simona; Nocella, Cristina; Cammisotto, Vittoria; Castellani, Valentina; Parisella, Raffaele; Meo, Irene Di; Carnevale, Roberto; et al. (Archives of Clinical and Biomedical Research, 2025)
Objective: To investigate the ADA score for major adverse cardiovascular events (MACE) prediction in patients with atrial fibrillation (AF) on anticoagulation. Patients and Methods: This is a prospective cohort study including patients with AF receiving anticoagulant therapy from 2013 to 2023 if they consented to participate in the study. Principal endpoint was MACE occurrence – including non-fatal acute myocardial infarction, nonfatal acute ischemic stroke, non-fatal acute peripheral artery event, and cardiovascular death – during 1-year follow-up. Patients were divided into low (ADA score <49), and high risk (ADA score ≥ 49). Results: Twenty-one out of 1000 patients (2.1%) experienced a MACE. Patients with MACE were older, more frequently affected by coronary artery disease, had lower albumin, higher D-dimer, and higher ADA score values compared to patients without MACE. High-risk patients had more often arterial hypertension, heart failure, and a history of stroke. Patients at higher risk had a significantly greater risk of MACE compared to lowrisk patients (risk ratio, 3.39; 95% confidence interval, 1.23-9.32). The c-statistic of ADA score was 0.67 (95% confidence intervals, 0.54 to 0.77) with a sensitivity of 86% (95% confidence intervals, 43% to 99%), and a specificity of 50% (95% confidence intervals, 46% to 94%). Conclusions: The ADA score has a good performance for MACE prediction in patients with AF. A more aggressive management of cardiovascular risk factors and comorbidities should be warranted for at-risk patients as identified by ADA score ≥ 49.